The Political Sociology and Anthropology of Evil - Horváth, Ágnes. (London)
1 online resource (225 p.).
Keywords: This book offers a new approach to the problem of evil through an examination of the anthropological figure of the trickster'. A lesser known and much more recent term than evil, the authors use the trickster to facilitate a greater understanding of the return of evil in the modern era. Instead of simply opposing good' and evil', the figure of the trickster is used to pursue the trajectories of similarities and quasi-similarities through imitation. After engaging with the trickster as presented in comparative anthropology and mythology, where it appears in tales and legends as a strange, erratic outsider, the authors seek to gain an inside perspective of trickster knowledge through an examination of mythology and the classical world, including both philosophers and poets. The book then goes on to trace the trickster through prehistory, using archaeological evidence to complement the diverse narratives. In this way, and by investigating the knowledge and customs surrounding evil, the authors use the figure of the trickster to provide an unprecedented diagnosis of the contemporary world, where external, mechanical rationality has become taken for granted and even considered as foundational in politics, economics, and technologised science. The authors advance the idea that the modern world, with its global free markets, mass mediatic democracy and technologised science, represents a universalisation of trickster logic. The Political Sociology and Anthropology of the Evil will be of interest to scholars working in the fields of social theory, political anthropology and political sociology, as well as those interested in the ways in which evil can infiltrate reality.